2021
DOI: 10.1021/acs.langmuir.1c01844
|View full text |Cite
|
Sign up to set email alerts
|

Biphilic Surfaces with Optimum Hydrophobic Islands on a Superhydrophobic Background for Dropwise Flow Condensation

Abstract: Sustaining dropwise condensation is of great importance in many applications, especially in confined spaces. In this regard, superhydrophobic surfaces enhance condensation heat transfer performance due to the discrete droplet formation and rapid removal. On the other hand, droplets tend to nucleate easier and faster on hydrophobic surfaces compared to superhydrophobic ones. To take advantage of the mixed wettability, we fabricated biphilic surfaces and integrated them to small channels to assess their effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Employing the spraying method for fabrication has made the manufacturing process of these surfaces cost-effective. In addition, in most of the studies in the literature, the best performance of the engineered surfaces was at relatively low subcooling temperatures. ,, However, the fabricated coating in this study showed its best ability at a subcooling temperature of 25.5 °C; therefore, this coating is applicable where a high subcooling temperature is required. Furthermore, the performance of the proposed surfaces in the industry has been investigated experimentally through various tests.…”
Section: Introductionmentioning
confidence: 69%
“…Employing the spraying method for fabrication has made the manufacturing process of these surfaces cost-effective. In addition, in most of the studies in the literature, the best performance of the engineered surfaces was at relatively low subcooling temperatures. ,, However, the fabricated coating in this study showed its best ability at a subcooling temperature of 25.5 °C; therefore, this coating is applicable where a high subcooling temperature is required. Furthermore, the performance of the proposed surfaces in the industry has been investigated experimentally through various tests.…”
Section: Introductionmentioning
confidence: 69%
“…Recent works also demonstrated various strategies to fabricate scalable biphilic surfaces. 41,42 Artificial nucleation cavities have also been incorporated to enhance HTC in flow boiling where boiling occurs inside micro and mini channels. 43 Recently, anti-icing surfaces utilizing controlled nucleation of ice on sacrificial structures have been developed.…”
Section: Engineered Nucleation Sitesmentioning
confidence: 99%
“…Hoque et al 40 showed that proper design of the biphilic surface can significantly enhance the condensation heat transfer performance. Recent works also demonstrated various strategies to fabricate scalable biphilic surfaces 41,42 . Artificial nucleation cavities have also been incorporated to enhance HTC in flow boiling where boiling occurs inside micro and mini channels 43 .…”
Section: Static Surface Structures and Chemistrymentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] However, these biphilic surfaces often involve complex geometries requiring precisely geometries design, multiple fabrication steps, and sophisticated equipment that make scaling up difficult and expensive. [34][35][36][37] Herein, instead of relying on structural manipulation, the water-repellent coatings of the superhydrophobic surfaces were tailored in this study to attain rapid droplet nucleation while retaining sufficient repellency to maintain jumping droplet departure. Inspired by the reports that soft, deformable surfaces promote water nucleation, [38,39] branched siloxanes (Siloxane2) with hydrophilic and hydrophobic molecular segments were prepared.…”
Section: Introductionmentioning
confidence: 99%